Seasonality of occurrence and recruitment of Arctic marine benthic invertebrate larvae in relation to environmental variables - Kuklinski, Piotr; Berge, Jørgen; McFadden, Laurel; Dmoch, Katarzyna; Zajaczkowski, Marek; Nygård, Henrik Andreas; Piwosz, Kasia; Tatarek, Agnieszka (Polar Biology, 2013)
The Arctic system is one of the regions most influenced by ongoing global climate change, but there are still critical gaps in our knowledge regarding a substantial number of biological processes. This is especially true for processes taking place during the Arctic winter but also for seasonal processes, such as the dynamics of intra-annual meroplankton occurrence. Here, we report on a 1-year study of meroplankton seasonal variability from a fjordic system in the Arctic Archipelago of Svalbard. The study combines an examination of phytoplankton, zooplankton, and hard bottom benthic settlement with measurements of environmental parameters (e.g., water temperature, particulate organic matter, and dissolved organic carbon). Samples were taken on a bi-weekly or monthly basis, and a total of 11 taxa representing six phyla of meroplankton were recorded over a 1-year period from January to December 2007. The occurrence of benthic larvae varied between the seasons, reaching a maximum in both abundance and taxon richness in late spring through early summer. Meroplanktonic larvae were absent in winter. However, settlement of benthic organisms was also recorded during the winter months (February and March), which indicates individual trade-offs related to timing of reproduction and competition. In addition, it suggests that these larvae are not relying on higher summer nutrient concentrations, but instead are dependent on alternative food sources. In parallel with meroplankton abundance, all other measured parameters, both biological (e.g., phyto- and zooplankton abundance and diversity) and physical (e.g., particulate organic matter), exhibited seasonal variability with peaks in the warmer months of the year.